(3eSdSd CFeI GdgOis (3GdEeGe GdHNGQj(B.s - (3eLehYI GdNdjaI ddceHjhJQ(B.s ((3GdbGgQI (B:s (3eLehYI NdjaI ddceHjhJQ(B.s)
(3YOOGdMdbGJ(B1.s
(3SjfGQjh hMhGQ Cjef SdGeI(B- (3ENQGL MeOj GdfHhj (B.s
1 vcd (3eSdSd GFeI GdGSdGe (B.s
All age.
Keywords: (3GdJeKjd GdOQGejs -- (3JdjaRjhf(B.s